Literatur Review Elastisitas Penawaran Tenaga: Studi Empiris Pengujian Hipotesis Neoklasik dan Reference Dependent Preference - Wirya Wardaya; Mohammad Wahed (Journal of Economics Development Issues, 2022)
The extent to which wage levels affect labor supply is an important topic in labor economics. Empirical research is conducted to prove how the elasticity of labor supply in response to changes in the wage rate is whether the neoclassical hypothesis or the reference dependent-preference hypothesis applies. This study reviews the growth of empirical literature of the reference-dependent preference hypothesis in the 2017-2022 period to enhance the critical review that was presented in the literature review section based on early journals in 1997 - 2011. The results of this review found that it rejects the neoclassical labor supply elasticity hypothesis and states that it is the reference-dependent preference hypothesis ABSTRAKSejauh mana tingkat upah mempengaruhi penawaran tenaga kerja merupakan topik penting dalam ekonomi ketenagakerjaan. Penelitian - penelitan empiris dilakukan untuk membuktikan bagaimana elastisitas penawaran tenaga kerja sebagai respon atas perubahan tingkat upah apakah yang berlaku adalah hipotesis neoklasik atau hipotesis reference dependent-preference. Penelitian ini mereview perkembangan referensi empiris pada hipotesis reference dependent preference pada periode 2017 – 2022 dari review kritik yang sudah disajikan pada bagian Kajian literatur berdasarkan jurnal awal mengenai pengujian reference dependent prefererence tahun 1997 - 2013. Hasil review ini menemukan bahwa dalam perkembangan kajian menemukan bahwa menolak hipotesis elastisitas penawaran tenaga kerja neoklasik dan menyatakan yang berlaku adalah hipotesis reference dependent preference.